1997
DOI: 10.1063/1.593498
|View full text |Cite
|
Sign up to set email alerts
|

Negative thermal expansion of fullerite C60 at liquid helium temperatures

Abstract: The thermal expa11sion of fullerite C 60 has been measured in the temperature range 2-9 K. A compac.t~d fullcrite sample with a diameter of about 6 mm and height of 2.4 mm was used. It was found that at temperatures below-3.4 K the linear thermal expansion coefficient becomes negative. At temperatures above S K our results are in good agreement with the available literature data. A qualitative cxplaPation of the results is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 17 publications
(9 reference statements)
0
31
0
Order By: Relevance
“…Negative linear thermal expansion coefficients at low temperatures have already been documented for pure fullerite [21] and also for fullerite intercalated with neon, argon, and krypton [17,23] and now, in conjunction with this work, with Xe as well [23]. The dilatometric measurements of thermal expansion coefficients in the orientational glass region of the C 60 -Xe system have been carried out up to 28 K. Which allowed comparison between dilatometric of Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Negative linear thermal expansion coefficients at low temperatures have already been documented for pure fullerite [21] and also for fullerite intercalated with neon, argon, and krypton [17,23] and now, in conjunction with this work, with Xe as well [23]. The dilatometric measurements of thermal expansion coefficients in the orientational glass region of the C 60 -Xe system have been carried out up to 28 K. Which allowed comparison between dilatometric of Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery of the fullerite molecule C 60 [1], the low-temperature physical properties of fullerite C 60 have been investigated by various methods: inelastic neutron scattering [2,3], infrared and Raman spectroscopy [4,5], x-ray [3,6,7], neutron [8] and electron [9,10] diffraction, NMR [11], dilatometry [12][13][14][15] and calorimetry [16][17][18][19][20][21][22][23][24][25]. It has found that fullerite C 60 is a molecular crystal in which the molecules are bonded by the van der Waals forces and its physical properties are largely determined by the dynamics of the rotational motion of the C 60 molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements were made in the interval 2.2-43 K using a low temperature capacitance dilatometer with a sensitivity of 0.02 nm. The dilatometer design and the measuring technique are detailed in [19]. Prior to measurement, the cell with the sample of pressure-oriented SWNTs was evacuated at room temperature for 72 h to remove possible gas impurities.…”
Section: Experimental Techniquementioning
confidence: 99%